2012
DOI: 10.1021/jf3026524
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drying of Jujubes (Ziziphus jujuba Mill.) on the Contents of Sugars, Organic Acids, α-Tocopherol, β-Carotene, and Phenolic Compounds

Abstract: This study investigated the changes in sugars, organic acids, α-tocopherol, β-carotene, phenolic profiles, total phenolic content (TPC), and antioxidant capacity of jujube fruits after four drying treatments (sun-, oven-, microwave- and freeze-drying). Sugar, organic acid, phenolic compounds, α-tocopherol, and β-carotene were qualitatived and quantitatived by high-performance liquid chromatography. The TPC and antioxidant activity of jujube samples were evaluated using the Folin-Ciocalteau method and 2,2'-azin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
133
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(167 citation statements)
references
References 30 publications
(62 reference statements)
22
133
0
3
Order By: Relevance
“…Previous studies on the impact of different drying techniques on the antioxidant activity of fruit confirm our results (Gao et al, 2012;Chong et al, 2013;Annegowda et al, 2014). Significant reductions in the antioxidant activity of jujube fruit in ABTS from oven-and sun-drying methods were reported in a previous study (Gao et al, 2012).…”
Section: Antioxidant Activitysupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies on the impact of different drying techniques on the antioxidant activity of fruit confirm our results (Gao et al, 2012;Chong et al, 2013;Annegowda et al, 2014). Significant reductions in the antioxidant activity of jujube fruit in ABTS from oven-and sun-drying methods were reported in a previous study (Gao et al, 2012).…”
Section: Antioxidant Activitysupporting
confidence: 91%
“…Significant reductions in the antioxidant activity of jujube fruit in ABTS from oven-and sun-drying methods were reported in a previous study (Gao et al, 2012). Chong et al (2013) reported that the heat pump, heat pump vacuummicrowave, hot air vacuum-microwave and hot air-cold air drying methods significantly reduced the DPPH antioxidant activities of apple, papaya and mango.…”
Section: Antioxidant Activitymentioning
confidence: 58%
“…San and Yildirim (2010) analyzed four varieties of four jujube fruits, and b-carotene was present at a level from 7 to 35 mg/100 g based on fresh weight, whereas the amount of carotenes was from 4.12 to 5.98 mg/100 g of dry weight as reported by Guil-Guerrero et al (2004). It was also shown that a much higher amount of b-carotene (15.6 mg/100 g) could be retained by freeze-drying (Gao et al 2012). …”
Section: Organic Acids and Carotenoidsmentioning
confidence: 85%
“…The same trend was registered for malic, lactic and tartaric acid. Oxalic acid was recorded in white maturity of fruits in Gao et al (2012) showed that ascorbic acid values were positively correlated with hardness in ten promising jujubes. The highest value in ascorbic acid of jujube fruits was recorded in harvested fruit at fully mature stage (637 mg/100g FW), by Moradinezhad et al (2016).…”
Section: Organic Acid Contentmentioning
confidence: 99%